PENGARUH PERMAINAN HURUF PUNGGUNG BERANTAI TERHADAP MOTIVASI BELAJAR ANAK DALAM MENULIS HURUF USIA 5-6 TAHUN DI RA AL-AMIN DURI - Richi Novelia N Novelia N; Daviq Chairilsyah Chairilsyah; Enda Puspita Puspita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Based on the results of preliminary observations in RA Amin Al-Duri, in learning magazines media always use early childhood. This instructional media used by teachers almost every day and causing her special children's learning motivation in writing the letter to be low as the lack of enthusiastic children in the activities of writing letters, the child looks bored in the activities of writing letters, and many children do not finish writing letters activities given by the teacher . So that the results obtained from the learning becomes less than optimal. To increase motivation to learn her special child in writing letters, researchers used a game. The purpose of this study was to determine whether there was an effect chain backs letter game against the child's learning motivation in writing the letter aged 5-6 years in RA Al-Amin Duri. The population in this study was the son of RA Al-Amin aged 5-6 years in B2 class of 20 children were held in April 2014. Data collection methods used in this study is the observation of pre-test and post-test. Data analysis was performed using t-test statistics with SPSS for windows release.17. From the results obtained, there are significant differences between children's learning motivation in writing the letters before and after treatment. It can be seen from the price of t -24 314 crashed at the reception Ha when the price t table = 1.734 and using test two parties with 5% error level. Based on the results of observational data processing motivation to learn to write letters pre-test and post-test, the pre-test phase obtained a percentage of 48.54%. After being given a treatment in the form of the game back a chain letter, the post-test phase obtained a percentage of 82.91%. This suggests that the motivation to learn to write letters rose by 34.37%. Keywords: motivation to learn, letters game